Joint inhomogeneity in dissimilar friction stir welded martensitic and nanostructured ferritic steels. (17th November 2018) - Han, Wentuo; Wan, Farong; Yabuuchi, Kiyohiro; Serizawa, Hisashi; Kimura, Akihiko
ABSTRACT: Dissimilar welding between oxide dispersion strengthened ferritic (ODS) steel and reduced activation martensitic steel would be required for constructing the advanced blanket of progressive fusion reactors. In this study, we achieved dissimilar joints by friction stir welding, and aimed to characterise and ameliorate joint inhomogeneity. Main results reveal that the joint inhomogeneity is generated from discrepant microstructural evolutions within the martensitic and ODS ferritic steels. The ODS steel achieves evolution by the dynamic recrystallisation, while the martensitic steel undergoes phase transformation that drastically hardens the stir zone. By a proper post-weld heat treatment, the joint inhomogeneity can be effectively ameliorated due to carbide reprecipitation and stress relief in the joint.